Media Pembelajaran Video Animasi Legenda Putri Mandalika Berbasis Artificial Intelegence - Putra, Yupi Kuspandi; Hasanah, Sosiatul; Fathurrahman, Fathurrahman; Hidayat, Muh. Adrian Juniarta (Fakultas Teknik Universitas Hamzanwadi, 2025)
The rapid development of information technology has brought significant changes in various aspects of life, including in the field of education. The need for effective and efficient learning media is increasingly urgent along with demands to improve the quality of education that is relevant to current developments. The Legend of Putri Mandalika is one of the Indonesian cultural heritages rich in moral values and local wisdom. However, delivering traditional legend stories to the younger generation today still faces challenges, especially in terms of engaging learning methods that are relevant to current digital technology developments. This study aims to produce a 3D animation-based learning medium that presents the story of the Legend of Putri Mandalika by utilizing Blender software and artificial intelligence (AI) technology to support the production process, including character creation, storyboard development, and voice-over. The method used includes pre-production, production, and post-production stages, each designed to maximize the visual and narrative potential of this legend. The final result of this study is a short animated video that can be used as an interactive learning medium for elementary to junior high school students. Thus, the integration of 3D animation with AI technology is not only an innovative solution in developing learning media but also plays an important role in preserving local culture so that it remains alive and relevant in the digital era. This learning medium is expected to increase students’ learning interest, strengthen their understanding of cultural values, and encourage the positive use of technology in educational settings.